TINJAUAN PENGGUNAAN MEDIA SOSIAL SEBAGAI EFEKTIVITAS KOMUNIKASI PEMASARAN PERSPEKTIF ISLAM (Studi Kasus Pada Pedagang di Pasar Aceh) - Yusniar Yusniar (Sekolah Tinggi Ilmu Syariah (STIS) Al-Aziziyah Sabang, 2022)
The role of social media is important in various fields of activity, including business activities. Social media has changed the way we communicate today. Social media marketing is a powerful way for businesses of all sizes to reach prospects and customers. The use of social media can be more effective for conducting marketing communications by entrepreneurs. In this study, the respondents were entrepreneurs in the pasar Aceh as a community shopping center in Banda Aceh. This research is a quantitative research, while the data sources of this research are primary and secondary data obtained from questionnaires. Determination of the sample using purposive sampling method with a sample of 100 respondents, the model used is a simple linear regression model. The results of this study indicate that the use of social media (X) has a significant effect on the effectiveness of marketing communications (Y) on islamic perspective.Keyword: Social Media. Marketing Communication, Islamic Entrepreneurship